(untitled) (Jurnal Geomine, 2015)
Measurement mining slope is very important in the advancement of the mine, but we always find obstacles when collecting data in the field, which does not fit the field conditions with the output data or data processing. This study aimed to minimize the aberrations that occur in mining slope measurement using a total station at PT. Antam (Persero). Tbk UBPN SULTRA. The method used in this research was done by total station is placed on top and the firing point bench peg/imaginary point cut made perpendicular to the plane or the object to be measured. The data used in this study, the slope measurement data mining by researchers and surveyors. Measurement slope mining results in differences in each measurement, the laying of the point peg, so that the angle formed at the incision B1 to B2 between measurements surveyor with researchers difference 13o, while the incision others although the point peg/ imaginary is not perpendicular to the plane, the slope formed almost in accordance with the conditions in the field by a margin slope of 1o-2o, and the slope of the incision B1 to B2 by researchers with a slope of 63o does not meet the standard of safety slope mining because the area of research done in the area of Mine South , namely high bench 5 meters and a slope of 60o, so the methods of measurements made researchers somewhat closer to the field conditions in accordance with data produced to minimize deviations in measurement